Model predora in simulacija prezračevanja v primeru požara - Modic, Jurij (Strojniški vestnik, 2003)
The catastrophic tunnel fires that have occured since 1999 and the series of accidents in some tunnels in the summer of 2001 have triggered extensive discussions and proposals relating to tunnel safety. When a fire occurrs in a tunnel, and in the absence of sufficient air supply, large quantities of smokeare generated, filling the vehicles and any space availabile arround them. Unless a strong flow is created and maintained, hot gases and smoke migrate in all directions. With a weak airflow, smoke forms a layer along the tunnel ceiling and can flow against the direction of forced ventilation, interfering with the evacuation of people from the tunnel. This paper describes a model of a tunnel and the results of a fire simulation in the tunnel. The model takes into account air velocity, air temperature and wall temperature during the fire. The simulation starts before the emergency ventilation system is activated and continues with the fans activated to control the smoke.
Keywords: predori cestni; požari; prezračevanje; simuliranje; predori; simulacija